Fighting corruption, promoting good governance (Commonwealth Secretariat LondonGB, 2000)
Clariefies the causes and consequences of poor governance and corruption. Identifies the elements of national strategies that countries could adopt to combat corruption effectively. Advocates a three-pronged approach based on the over-arching priniciple of zero tolerance, a) prevent corruption, b) enforce laws against it; and c) mobilise public opinion corrupt behaviour.
Keywords: CORRUPTION